Development of heterodyne receiver technology for sub-millimetre wavelength astronomy - Hector, A (2021)
Superconductor-Insulator-Superconductor (SIS) mixers are regularly employed as the detectors of choice in sub-millimetre wavelength astronomy receivers due to their unparalleled sensitivity, stable operation and ability to capture both amplitude and phase of incoming signals which is necessary to perform high-resolution spectroscopic observations. With the advent of telescopes such as the Atacama Large Millimetre/sub-millimetre Array (ALMA) which are set to explore the field for the foreseeable future, there is considerable interest in developing the technological capabilities employed by such facilities.